Disponibilidade de água e de nutrientes do solo e desenvolvimento do eucalipto em uma microbacia hidrográfica no município de Pinheiro Machado - RS. - Severo, Carlos Roberto Soares (2009)
The knowledge of the distribution of the soils allows the planning of agricultural activities in a way to maximize the productivity of cultures and reduce the environmental degradation. That way, the water and nutrient availability to the plants become of great importance and may be evaluated by means of physical, chemical and mineralogical analysis and its interpretation of local conditions. This study had the objective of surveying and mapping the soils of a hydrographic microbasin used in the culture of eucalyptus, relating its physico-hydrical and chemical characteristics with the culture development. The study area has 63,53 hectares and belongs to VPC Florestal, located in the Alamos Farm in the city of Pinheiro Machado, where the culture of eucalyptus saligna is being cultivated. To represent the mapping units were characterized in field and collected 9 soil profiles, representing the classes of Argisoils, Cambisoils, Chernosoils, Luvisoils and Neosoils. In relation to total nutrients, the class of soil that presented the greater quantity of available nutrients in t.ha-1 in the microbasin was the Cambisoil, followed by Luvisoil, Chernosoil, Neosoil and Argisoil. Relating to total nutrients, the class of soil that showed a greater quantity in t in the microbasin was the Argisoil, followed by the Neosoil, Luvisoil, Chernosoil and Cambisoil. The soils present in the hydrographic microbasin of the Alamos Farm have a total of 1300 basic available cations and a total of 15770 basic cations. As for the water availability, the Alamos Farm has a storing capacity in its soil of 121245m³ of water, of those 20778m³ available to the plants. Relating to the development of eucalyptus, the results show there was a differentiated growth in different soil mapping units, and the greater growth was showed in the class of Argisoil.